Peran Guru Mata Pelajaran Akidah Akhlak Dalam Menghadapi Era Digital di Madrasah Tsanawiyah Ecellent Zainul Hasan Balung Jember - Zuhro, Ika Nafisatus (IJIT: Indonesian Journal of Islamic Teaching, 2024)
Abstract: This journal aims to determine the role of Aqidah Akhlak subject teachers in facing the digital era at Madrasah Tsanawiyah Excellent Zainul Hasan Balung. The role of teachers, especially teachers of Aqidah Akhlak subjects in an educational institution, is very important. This refers to the aim of education which is one of the important aspects of life to form people of quality, character, responsibility and usefulness. This research uses a descriptive qualitative research approach. Data collection techniques using observation, interviews, documentaries. This research uses qualitative descriptive analysis. The results of this research are: 1). Teachers as educators include: (a) Religious inspirers, disciplinary inspirers. b) Religious motivator, discipline motivator. (c) Religious facilitator, discipline facilitator. 2) The teacher as a motivator, namely by instilling habitual character education, morning tadarus, reading Asmaul Husna, and welcoming students by the teacher at the front of the school gate to shake hands. 3) The teacher as an innovator in planning, namely using curmer to create teaching modules. In the implementation of learning the Aqidah Akhlak teacher uses 1 student 1 laptop as media.